Corporate social responsibility and employee citizenship behavior: The distinct moderating role of responsible leadership - Trinh, Ha; Tran , Ha Uyen Thi; Nguyen , Van Anh (Journal of Finance - Marketing Research, 2025)
This study investigates the effect of perceived corporate social responsibility (CSR) on employees’ organizational citizenship behavior and explores the moderating role of responsible leadership in the context of the luxury hotel industry in Vietnam. A quantitative research design was employed using p˙artial least squares structural equation modeling (PLS-SEM). Data were collected from 553 employees working in 21 five-star hotels in Vietnam. The results reveal that perceived corporate social responsibility positively influences both dimensions of organizational citizenship behavior: individual-directed (OCB_I) and organization-directed (OCB_O). However, perceived corporate social responsibility exerts a significantly stronger impact on OCB_O than on OCB_I. Moreover, responsible leadership demonstrates a selective moderating effect: it significantly strengthens the relationship between corporate social responsibility and OCB_O, while showing no significant influence on the corporate social responsibility - OCB_I link. The study contributes to the literature by simultaneously examining two distinct dimensions of organizational citizenship behavior, identifying the selective moderating role of responsible leadership, and extending corporate social responsibility- organizational citizenship behavior research to an emerging Asian context. These findings enrich the understanding of how corporate social responsibility perceptions translate into different forms of employee extra-role behaviors and highlight the contextual importance of leadership in the social exchange process. From this results, management implications have been proposed to effectively promote the hotel's corporate social responsibility policy and human resource management.